Freestanding midwifery units: Maternal and neonatal outcomes following transfer. (March 2017) - Monk, Amy R.; Grigg, Celia P.; Foureur, Maralyn; Tracy, Mark; Tracy, Sally K.
Abstract: Background: the viability of freestanding midwifery units in Australia is restricted, due to concerns over their safety, particularly for women and babies who, require transfer. Aim: to compare the maternal and neonatal birth outcomes of women who planned, to give birth at freestanding midwifery units and subsequently, transferred to a tertiary maternity unit to the maternal and neonatal, outcomes of a low-risk cohort of women who planned to give birth in, tertiary maternity unit. Methods: a descriptive study compared two groups of women with low-risk singleton, pregnancies who were less than 28 weeks pregnant at booking: women who, planned to give birth at a freestanding midwifery unit ( n =494) who, transferred to a tertiary maternity unit during the antenatal, intrapartum or postnatal periods ( n =260) and women who planned to give, birth at a tertiary maternity unit ( n =3157). Primary outcomes were mode, of birth, Apgar score of less than 7 at 5 minutes and admission to, special care nursery or neonatal intensive care. Key findings: the proportion of women who experienced a caesarean section was lower, among the freestanding midwifery unit women who transferred during the, intrapartum/postnatal period compared to women in the tertiary maternity, unit group (16.1% versus 24.8% respectively). Other outcomes were, comparable between the cohorts. Rates of primary outcomes in relation to, stage of transfer varied when stratified by parity. discussion: these descriptive results support the provision of care in freestanding, midwifery units as an alternative to tertiary maternity units for women, with low risk pregnancies at the time of booking. A larger study, powered, to determine statistical significance of any differences in outcomes, is, required.